Japan’s strategic interests in the South China Sea : beyond the horizon? - Koga, Kei (2020)
Japan has a national interest in the South China Sea issue. Although its direct commitment is ultimately limited in a material sense due to a lack of military capabilities, as well as political and constitutional constraints on the Self-Defense Force, Japan has maintained its firm stance to uphold international maritime rules and norms, and nurtured strong diplomatic relations and conducted maritime capacity-building programs with the South-East Asian states, as well as the Association of Southeast Asian Nations. These actions contribute to consolidating the rule of law at sea and provide those claimant states an opportunity to withstand pressures from China. Given the Trump administration’s unclear South China Sea policy and South-East Asia’s strategic uncertainty, Japan is becoming a key player in maintaining regional maritime stability in East Asia through diplomacy.